Reproductive Health Education in Improving Adolescents' Self-Protection Against Sexual Abuse: A Scoping Review - Natasya Fauziah Malik; Andari Wuri Astuti; Islamiyatur Rohmah (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: The issue of sexual abuse among adolescents remains a reproductive health issue, and adolescents' vulnerability increases due to a lack of knowledge about self-protection. This scoping review aims to identify and map scientific evidence regarding reproductive health education in improving adolescents' self-protection skills against sexual abuse.Method: : This scoping review follows the PRISMA-ScR guidelines and uses the PCC (Population, Concept, Context) Framework. Literature searches were conducted using five databases, namely PubMed, ScienceDirect, Wiley Online Library, EBSCO, and Google Scholar. The article screening process was carried out systematically using Rayyan, with duplicate removal, title and abstract screening, and full-text assessment against inclusion and exclusion criteria. Of the 854 articles identified, 10 articles met the criteria and were analyzed further. The methodological quality of the articles was assessed using the Joanna Briggs Institute (JBI) assessment, with 7 articles (70%) receiving a Grade A and 3 articles (30%) receiving a Grade B. The dominant research designs were pre-experimental (30%) and qualitative (30%).Result: This scoping review identified four themes, namely adolescents' knowledge of reproductive health, reproductive health education in schools, educational materials and methods, and improving adolescents' self-protection skills. Reproductive health education shows potential in supporting the strengthening of adolescents' self-protection against sexual abuse through increasing their knowledge and protective skills.